2020
DOI: 10.1107/s1600576720000643
|View full text |Cite
|
Sign up to set email alerts
|

RADDOSE-XFEL: femtosecond time-resolved dose estimates for macromolecular X-ray free-electron laser experiments

Abstract: For macromolecular structure determination at synchrotron sources, radiation damage remains a major limiting factor. Estimation of the absorbed dose (J kg−1) during data collection at these sources by programs such as RADDOSE‐3D has allowed direct comparison of radiation damage between experiments carried out with different samples and beam parameters. This has enabled prediction of roughly when radiation damage will manifest so it can potentially be avoided. X‐ray free‐electron lasers (XFELs), which produce i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 61 publications
1
23
0
2
Order By: Relevance
“…For reference, we therefore used an updated version of RADDOSE (RADDOSE-XFEL), which now also offers to correctly calculate XFEL as well as SSX doses. We estimated the average dose in the exposed region, indicating that the 80 kGy dose limit was exceeded by a factor of ~2 for the SSX data (Table II) 44 . (Figure 3).…”
Section: Radiation Damagementioning
confidence: 99%
See 1 more Smart Citation
“…For reference, we therefore used an updated version of RADDOSE (RADDOSE-XFEL), which now also offers to correctly calculate XFEL as well as SSX doses. We estimated the average dose in the exposed region, indicating that the 80 kGy dose limit was exceeded by a factor of ~2 for the SSX data (Table II) 44 . (Figure 3).…”
Section: Radiation Damagementioning
confidence: 99%
“…Doses for each dataset were calculated using the software RADDOSE-3D (v. 4.0) and its subprogram RADDOSE-XFEL, respectively 44 Table II. Isomorphous difference maps were calculated in analogy to a previously published approach scaling the datasets to their resolution shells 45 .…”
Section: Dose and Radiation Damagementioning
confidence: 99%
“…This means that the dose is likely to be slightly overestimated, as it is in standard RADDOSE‐3D calculations. However, models have shown that for an “average protein,” there is an average of one ionization per atom at a dose of ~400 MGy 24,40 . Since the experimental dose limit of 30 MGy for synchrotron studies is an order of magnitude below this, 8 it is unlikely in practice that a significant number of atoms are ionized at any stage of the diffraction experiment, so the anticipated error due to this treatment is minimal.…”
Section: Description Of the Programmentioning
confidence: 99%
“…This paper reports an extension of RADDOSE‐3D to perform full Monte Carlo simulations of a rotating crystal during MX experiments, which comprehensibly track the path and energy loss of photoelectrons and Compton recoil electrons produced both in the crystal and the surrounding material. This version (version 4), which includes an option for estimating time‐resolved doses for experiments using femtosecond pulses at Free Electron Lasers 24 supersedes previous releases of the software. The simulations are presented, including an investigation of the conditions under which these provide more accurate dose estimates than previous versions of RADDOSE‐3D (v1–v3).…”
Section: Introductionmentioning
confidence: 99%
“…Для конкретных образцов массовый коэффициент поглощения либо рассчитывается, используя табуированные значения сечений поперечного рассеяния для разных химических элементов (например, с помощью International Tables for Crystallography или с помощью сервера https://physics.nist.gov/PhysRefData/Xcom/html/xcom1.html), либо измеряется в эксперименте[49]. Для расчёта радиационной дозы можно также воспользоваться программой RADDOSE-3D[50,51] или недавно усовершенствованным вариантом этой программы для экспериментов на лазерах на свободных электронах RADDOSE-XFEL[52].В макромолекулярной кристаллографии широко используется оценка для предельного значения дозы, так называемый предел Хендерсона, равный 30•10 6 Гр Математическая биология и биоинформатика. 2020.…”
unclassified